Evaluation of Native Species of Entomopathogenic Nematode, Steinernema dharanaii Kulkarni et al., 2012 (TFRIEPN) against Bamboo Leaf Roller, Crypsipyta coclesalis Walker (Lepidoptera: Pyralidae) in the Laboratory - Paunikar, Sanjay; Kulkarni, Nitin (Indian Forester, 2019)
The bamboo leaf roller, Crypsiptya coclesalis is the major pest of bamboo species in central India. Several bio-pesticides have been tested for the management of bamboo leaf roller in different parts of the country, but only few have shown promising results. Entomopathogenic nematodes are emerging as potent biocontrol agent against various insect pests. The laboratory studies were carried out to evaluate the efficacy of an indigenous species of Steinernema dharanaii (TFRIEPN-15) against fourth instar larvae of bamboo leaf roller. In laboratory conditions the efficacy of EPN was tested at nine dosages viz., 3, 5, 10, 15, 20, 30, 40 50, and 100 IJs Larva-1 plate. The doses of 3 IJs Larva-1 exhibited negligible but statistically significant mortality (19.99%) over untreated control (P<0.05), but at par with 5 IJs Larva-1 (28.56%). It was followed by mortalities at 10, 20, 30, 40 and 50 IJs Larva-1, respectively with 42.85, 48.56, 54.28, 62.85 and 68.56 % mortality, which were statistically at par with each other (P>0.05). The probit analysis performed, indicated 9.24 (UL 13.76 and LL 6.21 IJs Larva-1) and 39.62 IJs Larva-1 (UL 58.93 and LL 26.64 IJs Larva-1) were required to cause, respectively 50 and 90.0 % mortality in bamboo leaf roller larvae in laboratory. The production of IJs in progeny was maximum in 50 IJs larva-1 (8,040 IJs Larva-1), above which it showed sharp decline in progeny production due to false infections. These results encourage the possibility of using entomopathogenic nematode for biological control of insect pests of forestry and agricultural importance.